INTEGRATION PROCESSES IN THE FINANCIAL SPHERE BETWEEN THE OTTOMAN EMPIRE AND FRANCE (the second half of the XIX century) (Journal of history, 2019)
One of the main indicators of the strength and power of world empires in the XIX century is the development of the economic sphere; each empire applied the prospect of development of its economy. To this end, the strengthening of foreign trade, the development of industry, the banking and financial-credit sectors were taken into account, since the search for colonies and tax collection from underdeveloped countries was no longer so important. In addition, world empires have come closer to each other in the economic sphere, and also established strong ties in other sectors of economy. Relations in the financial sector, considered one of the main areas of the economy in the second half of the XIX century, had a particularly important role in the international economy. Such ties in the financial sphere were established between the Ottoman Empire and France, which was the main player in the European economy. This scientific article discusses the history of cooperation in the financial sphere between the Ottoman Empire and France in the second half of the XIX century. A scientific analysis will be conducted regarding financial integration between the two empires, as well as its development process and directions. Also, one of the main objectives of the article is the study of economic projects implemented in the credit sector, their progress and results.